Nursing Teaching from the axiological position of the university teacher. (Salud, Arte y Cuidado, 2024)
The purpose of this argumentative/reflexive essay is to address the teaching of nursing from the axiological position of the university teacher. The university campuses are in charge of imparting the pertinent technical-scientific knowledge to the students, but it is also of vital importance that values ​​are implicit in the contents of the curricular axis. For this reason, university teachers are the architects of transmitted knowledge, today the teacher is professional whose didactic and pedagogical skills are focused on the formation of competencies, abilities, skills, attitudes and aptitudes, which will allow their students to have domains and capabilities for research, development, innovation and entrepreneurship. he teacher, through his experience, manages to transcend his learning towards nursing students, through values ​​such as empathy, respect, human quality and responsibility and, therefore, achieve significant learning.